Strategies for induction of ovulation for fixed-time AI in lactating dairy cows submitted to a novel presynchronization protocol - Consentini, Carlos Eduardo Cardoso (2019)
The study evaluated strategies for induction of ovulation for fixed-time AI (FTAI) in lactating dairy cows submitted to Ovsynch-type protocols initiated after a novel presynchronization strategy. A total of 909 lactating dairy cows from 6 dairy herds were at 36.7 ± 0.28 d in milk, with body condition score of 3.16 ± 0.02 when they underwent presynchronization. On D-15, all cows received an intravaginal progesterone (P4) implant of 1.0 g P4 (new or used) or a used device of 2.0 g P4 and 7 d later (D-8) the P4 implant was removed and cows received 1.0 mg i.m. estradiol cypionate (EC) and 0.530 mg i.m. sodium cloprostenol (PGF). On D0, a synchronization of ovulation protocol for FTAI was initiated and cows were randomly assigned to 1 of 3 experimental groups, that differed only on the strategy to induce ovulation at the end of the protocol. The protocols initiated on D0 with 16.8 μg i.m. of buserelin acetate (GnRH) concomitant with insertion of a 2.0 g (new or used) P4 device. On D6, every cow received 0.530 mg PGF followed by a second PGF on D7, concomitant with P4 device withdrawal. In Group EC, cows received 1.0 mg EC on D7 (time of P4 device withdrawal) as inducer of ovulation. In Group EC/G, cows received EC on D7 and 8.4 μg GnRH administered 16 h before FTAI (56 h after the first PGF). Finally, in Group G, cows only received 8.4 μg GnRH at 56 h after the first PGF. The FTAI was performed on D9 (48 h after P4 device withdrawal) in all experimental treatments and pregnancy diagnosis was performed 31 and 60 d after FTAI. The pregnancy per AI (P/AI) was not different between cows with or without CL on D-15 (44.7 vs. 38.7%) and on D0 (44.3 vs. 37.3), however, cows with CL on D6 had higher P/AI than cows without CL at PGF (45.9 vs. 17.7%). Estrus expression was greater in cows receiving EC compared to cows receiving only GnRH (80.0 vs. 46.1%). Moreover, cows expressing estrus had greater P/AI than cows not showing estrus on d31 (50.8 vs. 34.8) and on d60 (48.5 vs. 27.6%), however, estrus did not affect pregnancy loss. There were no differences between experimental treatments on P/AI on d30 with an overall P/AI of 40.4% (367/909). Pregnancy loss and P/AI on d60 did not differ between treatments. In conclusion, the reproductive program has potential to promote high fertility and the 3 strategies to induce the final synchronized ovulation produced similar fertility. Further research is needed to optimize the presynchronization strategy and to more definitively determine the effect of different methods of ovulation induction on P/AI and in particular on the pregnancy loss after the d30 pregnancy diagnosis.